A Facile Route to Ortho‐Hydroxyanilnes through an IrIII‐Catalyzed Direct C−H Amidation of 2‐Phenoxypyridines. Issue 19 (7th September 2017) - Wang, Lianhui; Yang, Zi; Yang, Mengqi; Tian, Miaodou; Kuai, Changsheng; Cui, Xiuling
Abstract: A highly efficient and regioselective Ir III ‐catalyzed C−H amidation of 2‐phenoxypyridines has been developed by using sulfonyl azides as an amino source. The amidated products were provided in good‐to‐excellent yields with broad functional‐group tolerance. Furthermore, the 2‐pyridyl moiety in the amidated products could be readily removed, thus offering an efficient route to synthetically useful ortho ‐hydroxyanilnes, which are important building blocks in organic synthesis. Abstract : Isn′t it Ir‐onic : A highly efficient and regioselective Ir III ‐catalyzed C−H amidation of 2‐phenoxypyridines with sulfonyl azides has been developed, which offers synthetically useful ortho ‐hydroxyanilnes after removal of the 2‐pyridyl moiety.